Regional Factor in Transnational Relations: the Experience of Latvia and Lithuania in the 1920s - Krēsliņš, Uldis (Acta humanitarica academiae Saulensis, 2019)
By the end of Latvia’s struggle for freedom, the Republic of Latvia, proclaimed in 1918, acquired land border with four countries: and if in separate stages Estonia or Poland became Latvia’s closest ally, then in the long term Latvia’s closest relation formed with its southern neighbour Lithuania. This article does not claim to be the comprehensive study of Latvian-Lithuanian relations in the 1920s; it focuses on certain important aspects and some less known details of these relations, which reflect their universality, versatility and some inconsistency. The main obstacle in relations between two countries in 1920s was difficult Lithuanian foreign policy situation – especially its open conflict with Poland. In these conditions, Latvia made attempts to dispel Lithuania’s suspicion of its intentions, and as an expression of its special friendship on February 1921, it was one of the first to give de iure recognition to Lithuania, but the Lithuanian political circles remained cautious about the intentions of Latvia. Political complications in the relations between the two countries were balanced by social aspirations of public organizations and associations to converge and society efforts starting in 1921 with the search for rapprochement. As early as 1921, Latvian-Lithuanian and Lithuanian-Latvian unity societies were established in Riga and Kaunas, which organized language courses and excursions to the neighbouring countries in order to bring both nations closer. The annual Latvian and Lithuanian Rapprochement Congresses held since 1924 were of particular importance: it became with special manifestation of social aspirations of both states, which would be difficult to find in all Europe during the interwar period; they contributed not only to cultural ties between the two nations, but also allowed the idea of a political union of the two countries to be supported in the form of the Baltic Kingdom. However, these aspirations and attempts for rapprochement failed to influence Lithuania’s internal policy, and at the end of 1920s the activities of Lithuanian political emigrants in Latvia became a new stumbling block in the relations between the two countries, putting the Latvian government in front of a complicated political choice. After the Congress of Lithuanian’s Political Emigrants, held in Riga on November 1927, which revealed the political contradictions of the emigrants themselves, the Latvian government stepped up measures to limit the political activities of Lithuanian emigrants. This government’s position was criticized by the Latvian Social Democrats and provoked sharp condemnation of assessing it as the desire to convince the Latvian government to please Lithuania, but the government chose the priority of the Statehood, sacrificing the ideals of democracy and human rights in this name. This dualism is the main feature that characterized relations between Latvia and Lithuania in the 1920s: if social aspirations, organizations and communities, public efforts tried to bring the two countries closer together, the complication in Lithuania’s foreign and internal (domestic) policies hindered the creation of closer political union of Baltic States. In this particular model of interstate relations, one should also look for an explanation of the different views on the relations between Latvia and Lithuania in the interwar period: if from the point of view of traditional interstate relations at the government level, one can agree with the opinion of some Latvian historians that Estonia was the only ally of Latvia, then in terms of public aspirations, Latvia’s closest relations were nevertheless associated with Lithuania.